(untitled) (Salud, Arte y Cuidado, 2018)
The study was carried out with the objective of evaluating the appearance of the withdrawal syndrome secondary to the prolonged use of opioids and benzodiazepines in neonatal and pediatric patients in the polyvalent intensive care unit (ICU) at the Pediatric Teaching Hospital “Agustin Zubillaga” (PTHAZ). It was developed in the positivist paradigm, a quantitative approach, within the framework of a descriptive study, under the modality of field research specifically of transversal nature. The study population was made up of seven (07) neonatal and pediatric patients who received prolonged (more than five days) opioids and benzodiazepines in the ICU of the PTHAZ. An instrument for data collection was applied to them. The Finnegan Scale was applied to neonatal patients. The Sophia Observation Withdrawal Symptoms Scale (SOS), was applied to pediatric patients. The analysis of the results was carried out through the Microsoft Excel program. These were showed in statistical charts and graphs. As a result, the neonatal and pediatric patients developed 100% SA after receiving fentanyl and/or midazolam for more than 5 days. The most frequent symptoms in the neonatal patients were: insomnia, excessive crying, increased Molar reflex, tremors, sweating, tachypnea, sneezing, excessive suction, inappetence and diarrhea. In pediatric patients it was observed that the most usual symptoms were: tachycardia, tachypnea, fever, anxiety, tremors, inconsolable crying, insomnia and diarrhea.